Safety and efficacy of a fixed-dose combination regimen of grazoprevir, ruzasvir, and uprifosbuvir with or without ribavirin in participants with and without cirrhosis with chronic hepatitis C virus genotype 1, 2, or 3 infection (C-CREST-1 and C-CREST-2, part B): two randomised, phase 2, open-label trials. (November 2017) - Lawitz, Eric; Buti, Maria; Vierling, John M; Almasio, Piero L; Bruno, Savino; Ruane, Peter J; Hassanein, Tarek I; Muellhaupt, Beat; Pearlman, Brian; Jancoriene, Ligita; Gao, Wei; Huang, Hsueh-Cheng; et al.
Summary: Background: There is a need for hepatitis C virus (HCV) therapies with excellent efficacy across genotypes and in diverse populations. Part A of the C-CREST-1 and C-CREST-2 trials led to the selection of a three-drug regimen of grazoprevir (MK-5172; an HCV NS3/4A protease inhibitor; 100 mg/day) plus ruzasvir (MK-8408; an NS5A inhibitor; 60 mg/day) plus uprifosbuvir (MK-3682; an HCV NS5B polymerase inhibitor; 450 mg/day). Part B of the studies tested this combination as a single formulation in different treatment durations in a broader population. Methods: Part B of these randomised, phase 2, open-label clinical trials enrolled individuals from 15 countries who were chronically infected with HCV genotypes 1–6 (HCV RNA ≥10 000 IU/mL) with or without compensated cirrhosis. Those with genotype 1, genotype 2, genotype 4, or genotype 6 were treatment-naive; those with genotype 3 could be treatment-naive or treatment-experienced with pegylated interferon and ribavirin. Randomisation occurred centrally using an interactive voice response system and integrated web response system. Participants were randomly assigned to receive treatment for 8, 12, or 16 weeks with a fixed-dose combination of grazoprevir, ruzasvir, and uprifosbuvir with or without ribavirin. The primary endpoint was the proportion of participants achieving sustained virological response 12 weeks after the end of all study therapy (SVR12), defined as HCV RNA less than the lower limit of quantification (either target detected unquantifiable or target not detected [<15 IU/mL]). The trials are registered atClinicalTrials.gov, numbersNCT02332707 andNCT02332720 . Findings: 676 participants were randomly assigned between Feb 18, 2015, and Aug 16, 2016. In all 675 participants who received at least one dose of study drug (full analysis set), SVR12 for the 8-week regimen of grazoprevir, ruzasvir, and uprifosbuvir with and without ribavirin was achieved in 39 (93% [95% CI 81–99]) of 42 participants with genotype 1a, 45 (98% [88–100]) of 46 with genotype 1b, 54 (86% [75–93]) of 63 with genotype 2, 98 (95% [89–98]) of 103 with genotype 3, and seven (100% [59–100]) of seven participants with genotype 4. SVR12 for the 12-week regimen with and without ribavirin was achieved in 87 (99% [95% CI 94–100]) of 88 participants with genotype 1, 61 (98% [91–100]) of 62 with genotype 2, and four (100% [40–100]) of four with genotype 6. Among participants with cirrhosis who were infected with genotype 3, SVR12 for the 12-week regimen with and without ribavirin was achieved in 28 (97% [95% CI 82–100]) of 29 of those who were treatment-naive and 29 (100% [88–100]) of 29 who were treatment-experienced. SVR12 for the 16-week regimen with and without ribavirin was achieved in 26 (100% [95% CI 87–100]) of 26 participants with genotype 2 infection and 72 (96% [89–99]) of 75 participants with genotype 3 infection. The most common adverse events were headache (143 [22%] of 664), fatigue (129 [19%] of 664), and nausea (83 [13%] of 664). 16 (2%) of 664 participants had serious adverse events. Interpretation: The combined regimen of grazoprevir (100 mg/day), ruzasvir (60 mg/day), and uprifosbuvir (450 mg/day) has the potential to provide a simplified treatment for HCV that is effective and well tolerated in most individuals infected with HCV, as well as a shorter duration of treatment in many individuals. Funding: Merck & Co, Inc.